The Role of the Principal in Motivating the Habituation of Dhuha Prayer and Fardhu Prayer in Congregation to Improve Student Discipline - Aulia, Nurul Affika; Madhakomala, R. (Indonesian Journal Publisher, 2024)
A leader is a person who stands in front of every institution or organization he leads, a leader who is trustworthy, sincere, visionary and always makes changes for the better. In the scope of the school, the principal is a leader who is digugu and imitated every action and behavior. This research uses a literature study method that analyzes several journal references as a reference in determining a good school principal. The purpose of this research is to study and analyze the results of previous findings related to the role of the principal in motivating the habituation of dhuha prayer and fardhu prayer in congregation to improve the discipline of students. Based on the results of the reference analysis, it shows that a principal has an important role in the running of a program held at school. Doing the habituation of dhuha prayer and fardhu prayer together with direct monitoring by the principal is very effective so that students run it with discipline.